Pengaruh Pemahaman dan Kesiapan terhadap Penerapan Standar Akuntansi Keuangan Entitas Mikro Kecil dan Menengah (SAK EMKM) pada UMKM Jenis Perdagangan dan Reparasi di Kabupaten Ponorogo - Zulfa Ainun Azizatu Rahmah; Khusnatul Zulfa Wafirotin; Iin Wijayanti (MAMEN: Jurnal Manajemen, 2024)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia are one of the priorities in national economic development. Therefore, reporting in this type of MSME business activity must be able to make systematic reports with the recording process following the applicable Financial Accounting Standards.  So, there needs to be an understanding and readiness factor in preparing the report, so that SAK EMKM can be implemented in the management of MSMEs. This research aims to determine the effect of understanding and readiness for SAK EMKM on Trade and Repair MSMEs in Ponorogo Regency. This type of research uses primary data in the form of data on the number of trade and repair type MSMEs in 2021. This research method is a quantitative descriptive approach. Meanwhile, the data analysis method uses data quality testing, regression analysis, and hypothesis testing, while data collection is by distributing questionnaires and interviews. The results of this research show that there is a significant influence of understanding and readiness factors on the implementation of SAK EMKM in Ponorogo Regency. This means that the government needs to pay more attention or provide outreach/direction regarding the preparation of financial reports to MSME actors in Ponorogo Regency in accordance with applicable financial standards.